1993
DOI: 10.1002/pssa.2211360134
|View full text |Cite
|
Sign up to set email alerts
|

Studies on ZnO/p-Si Heterojunctions Fabricated by a Modified CVD Method

Abstract: Thin film ZnO (≈0.7 μm) is deposited on quartz and p‐Si substrates by a modified CVD method. The optical and electrical properties of the film are studied. The ZnO/p‐Si heterojunction is characterized by current‐voltage and capacitance‐voltage measurements using indium ohmic contacts to zinc oxide. The conduction band and valence band discontinuity values are calculated and a suitable band energy diagram of the heterojunction is constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Thus the junction was found to be rectifying and the turn-on voltage is about 1.5 V. The maximum forward-to-reverse current ratio was found to be about 15. This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions.…”
Section: I-v Characteristicsmentioning
confidence: 50%
See 3 more Smart Citations
“…Thus the junction was found to be rectifying and the turn-on voltage is about 1.5 V. The maximum forward-to-reverse current ratio was found to be about 15. This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions.…”
Section: I-v Characteristicsmentioning
confidence: 50%
“…This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions. Basu et al 6 deposited ZnO films on p-Si substrate by chemical vapor deposition (CVD) technique and Ajimsha et al 19 prepared ZnO films by pulsed LASER deposition technique.…”
Section: I-v Characteristicsmentioning
confidence: 50%
See 2 more Smart Citations
“…Wu and Tseng [26] studied the influence of different diameters and densities of the nc-Au on the photocatalytic activity in Au/ZnO nanorod composites. Recently, Basu et al [27] reported on lowering the sensing temperature further to *100°C with surface modified (by Pd nanoparticles dispersion) ZnO thin films deposited by electrochemical process. But the limitation of this process is its incompatibility to standard CMOS process technology.…”
Section: Introductionmentioning
confidence: 99%